100 things every designer needs to know about people - Weinschenk, Susan (Berkeley, CA : New Riders, 2011)
Provides information and examples to help designers create products, applications, Web sites, and print materials that match the way people think and feel.
Includes bibliographical references (p. 225-234) and index.
Keywords: Design -- Psychological aspects